2003
DOI: 10.1161/01.atv.0000067701.09398.18
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasma Platelet-Activating Factor Acetylhydrolase Binds to All the Murine Lipoproteins, Conferring Protection Against Oxidative Stress

Abstract: Objective-Plasma platelet-activating factor (PAF) acetylhydrolase (AH) is an enzyme bound with lipoproteins that degrades not only PAF but also PAF-like oxidized phospholipids that are proposed to promote atherosclerosis. In this study, we investigated the distribution of PAF-AH protein among lipoprotein classes by using adenovirus-mediated gene transfer in mice, and we examined its effects on lipoprotein oxidation and foam cell formation of macrophages. Methods and Results-Adenovirus-mediated overexpression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 30 publications
2
43
0
2
Order By: Relevance
“…Several experimental studies have consistently demonstrated the capacity of HDL to modulate eNOS expression and to stimulate endothelial NO production in vitro and in vivo ( 10,13,15,(97)(98)(99). Moreover, in human studies, administration of reconstituted HDL has been shown to improve endothelial function in subjects with can hydrolyze oxidized phospholipids ( 77,78 ). In arteries of non hyperlipidemic rabbits, local expression of PAF-AH reduced the accumulation of oxidatively modifi ed LDL without changing plasma levels of PAF-AH and reduced the expression of endothelial cell adhesion molecules ( 79 ).…”
Section: Effects Of Hdl On Enos-dependent No Productionmentioning
confidence: 98%
“…Several experimental studies have consistently demonstrated the capacity of HDL to modulate eNOS expression and to stimulate endothelial NO production in vitro and in vivo ( 10,13,15,(97)(98)(99). Moreover, in human studies, administration of reconstituted HDL has been shown to improve endothelial function in subjects with can hydrolyze oxidized phospholipids ( 77,78 ). In arteries of non hyperlipidemic rabbits, local expression of PAF-AH reduced the accumulation of oxidatively modifi ed LDL without changing plasma levels of PAF-AH and reduced the expression of endothelial cell adhesion molecules ( 79 ).…”
Section: Effects Of Hdl On Enos-dependent No Productionmentioning
confidence: 98%
“…In vivo study in mice deficient for LDL receptor and leptin revealed that LCAT overexpression decreased autoantibodies to oxLDL (Mertens et al 2003). Besides LCAT and PON1, PAF-AH, another HDL-associated enzyme, nowadays also known as lipoproteinassociated phospholipase A2 (LpPLA2), is able to hydrolyze oxidized phospholipids (Marathe et al 2003;Noto et al 2003). The local expression of PAF-AH in arteries of non-hyperlipidemic rabbits reduced the accumulation of oxidatively modified LDL without changing plasma levels of PAF-AH and reduced the expression of endothelial cell adhesion molecules (Arakawa et al 2005).…”
Section: Mechanisms Under Physiological Conditionsmentioning
confidence: 99%
“…Inhibition of the enzymatic activity of Lp-PLA 2 rendered HDLs unable to prevent monocyte binding induced by oxidized LDLs in endothelial cells, and supplementation of the dysfunctional HDL particles with purified Lp-PLA 2 restored the normal protective function (Watson et al 1995b). In mice, adenovirus-mediated expression of human Lp-PLA 2 leads to a reduction in the autoantibody titers against oxidized LDLs and malondialdehyde (MDA)-modified LDLs (Quarck et al 2001;Noto et al 2003). Despite the fact that the antioxidative potential of HDL-bound Lp-PLA 2 has been well documented, several lines of evidence suggest that the presence of Lp-PLA 2 in LDL particles may actually stimulate atherogenesis.…”
Section: Inhibition Of Ldl Modification By Hdlsmentioning
confidence: 99%